(untitled) (Journal of Global Accounting, 2023)
The study ascertaines the relationship between firm financial characteristics and social responsibility cost of public industrial goods firms listed in Nigeria. Specifically, the study determines the extent to which firm total sales, firm total assets, firm financial leverage and firm profitability relate to public responsibility cost. The study adopts ex-post facto research design. From the sampling frame of 13 listed industrial goods firms, a sample size of 11 firms was purposively selected. Secondary data were collected from the annual reports of the sampled firms over a period of 10 years (2012-2021). In addition to diagnostic tests and descriptive tests, Pooled Ordinary Least Square was applied in estimating the regression model at 5% level of significance. The study found that: firm total sales have no significant but positive relationship with public responsibility cost of listed industrial goods firms in Nigeria (β = 0.322045, p-value = 0.0870); firm total assets have a significant positive relationship with public responsibility cost of listed industrial goods firms in Nigeria (β = 1.025267, p-value = 0.0007); firm financial leverage has no significant but positive relationship with public responsibility cost of listed industrial goods firms in Nigeria (β = 0.823169, p-value = 0.2199); firm profitability has a significant positive relationship with public responsibility cost of listed industrial goods firms in Nigeria (β = 2.045239, p-value = 0.0230). In conclusion, the findings that profitability has a significant positive relationship with corporate social responsibility supports the notion that more profitable firms have a greater ability to invest in social responsibility initiatives and are therefore expected to contribute more to society.The study recommended that policy makers should use incentives such as tax breaks or other financial benefits to encourage larger firms to invest in corporate social responsibility initiatives.